Numerical analysis of nitrogen adsorption and penetration depth in plasma-nitrided austenitic stainless steel 316: A crystallographic orientation study - J. Taghinejad; M. Vejdanihemmat; A. R. Niknam (AIP Advances)
The plasma nitriding process of austenitic stainless steels (ASSs) is numerically investigated by considering the effect of the crystallographic orientation on the physical parameters such as activation energy, diffusion coefficients, and processing temperature. The one-dimensional extended trapping–detrapping model is used, and the coupled differential equations due to diffused, trapped, and total concentrations are solved by the Crank–Nicolson finite-difference method. Moreover, the time evolution of the surface adsorption, surface concentration, and penetration depth is studied for (100), (110), and (111) facets separately. Results show that at constant plasma parameters, the highest surface nitrogen concentration is for (111), followed by (110) and (100). However, the penetration depth is highest for (100), followed by (110) and (111). It is demonstrated that the variation of the adsorption value for (100) is greater than those of (110) and (111) during the nitriding process. Our results agree with the experimental data, which can enhance the mechanical characteristics of ASSs.